Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline Terhadap Kemampuan Berpikir Kritis Siswa SMP pada Materi Tata Surya - Sri Wahyuni*; Zainur Rasyid Ridlo; Dwi Nova Rina (Universitas Syiah Kuala, 2022)
Articulate Storyline is software that can be used as a presentation media or communication tool. This interactive media does not require any programming knowledge during the creation process, because all animations can be created using the